⠀
Q56⟩⟩ If
, then x equals?
Answers
Answered by
71
Answer:
2 is the answer.
Step-by-step explanation:
HOPE THIS HELPS.
Attachments:
![](https://hi-static.z-dn.net/files/dd3/ab0db4efa038e38cc7a591c273e85818.jpg)
Answered by
103
Step-by-step explanation:
Given :-
(a/b)^(x-1) = (b/a)^(x-3)
To find :-
Find the value of x ?
Solution :-
Given equation is (a/b)^(x-1 )= (b/a)^(x-3)
It can be written as
=> (a/b)^(x-1) = 1/(a/b)^(x-3)
=> (a/b)^(x-1 )= (a/b)^-(x-3)
Since a^-n = 1/a^n
the bases are equal
=> The exponents must be equal
=> x-1 = -(x-3)
=> x-1 = -x+3
=> x+x = 3+1
=> 2x = 4
=> x = 4/2
=> x = 2
Therefore, x = 2
Answer:-
The value of x for the given problem is 2
Check:-
If x = 2 then
LHS = (a/b)^(x-1)
=>(a/b)^(2-1)
=> (a/b)^1
=>(a/b)------(1)
RHS =(b/a)^(x-3)
=>(b/a)^(2-3)
=> (b/a)^-1
=>1/(b/a)
Since a^-n = 1/a^n
=> (a/b) -----(2)
From (1)&(2)
LHS = RHS is true for x = 2
Verified the given relation.
Used formulae:-
- a^-n = 1/a^n
- 1/(a/b)=b/a
Similar questions